2010
DOI: 10.1002/sia.3247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen plasma on surface properties and biocompatibility of PLGA films

Abstract: In this study, poly(D, L-lactide-co-glycolide) (PLGA) films were prepared by solvent casting method and the surfaces of the films were modified by application of oxygen plasma. A radio frequency (RF) generator working at 13.56 MHz was used to create plasma, and powers at different levels changing between 20 and 300 W were applied. The variations in chemistry, topography and surface free energy (SFE) of the films were investigated by electron spectroscopy for chemical analysis (ESCA), atomic force microscopy (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…According to our knowledge, no literature on plasma treatment of polyglycolic acid has been published so far. However, quite a few research articles deal with plasma modification of the copolymer PLGA 122–130. In the past, mostly pure oxygen plasmas have been employed to modify the surface of PLGA 122, 123, 126, 130.…”
Section: Recent Achievements On Plasma‐based Surface Modification Of mentioning
confidence: 99%
See 2 more Smart Citations
“…According to our knowledge, no literature on plasma treatment of polyglycolic acid has been published so far. However, quite a few research articles deal with plasma modification of the copolymer PLGA 122–130. In the past, mostly pure oxygen plasmas have been employed to modify the surface of PLGA 122, 123, 126, 130.…”
Section: Recent Achievements On Plasma‐based Surface Modification Of mentioning
confidence: 99%
“…However, quite a few research articles deal with plasma modification of the copolymer PLGA 122–130. In the past, mostly pure oxygen plasmas have been employed to modify the surface of PLGA 122, 123, 126, 130. For example, Hasirci et al123 applied a low pressure oxygen RF discharge for the surface modification of 50/50 PLGA films and observed an increased hydrophilicity: the PLGA water contact angle decreased from 67° to approximately 38° after plasma treatment.…”
Section: Recent Achievements On Plasma‐based Surface Modification Of mentioning
confidence: 99%
See 1 more Smart Citation
“…However, quite a few research articles deal with plasma modification of the copolymer PLGA (Khorasani et al, 2008, Hasirci et al, 2010, Khang et al, 2002, Park et al, 2007, Park et al, 2010, Safinia et al, 2007, Safinia et al, 2008, Shen et al, 2008, Wang et al, 2004. 50/50 PLGA films were modified in an oxygen plasma at low pressure and a decrease of the contact angle from 67° to below 40° after plasma treatment was observed.…”
Section: Plasma Treatment Of Biodegradable Polymersmentioning
confidence: 99%
“…The characterization study indicated that the surface composition and the functional groups on the surface of PLLA and PHBV after plasma treatment had a great effect on cell affinity of these films 17 . In a comparative study, Croll et al 17 and Hasirci 19 studied the plasma etching effect on PLGA. The results showed an increase of hydrophilicity of PLGA membranes.…”
Section: Introductionmentioning
confidence: 99%